Endoscopic transpapillary bile duct biopsy with the combination of intraductal ultrasonography in the diagnosis of biliary strictures. Issue 3 (1st March 2002) - Tamada, K; Tomiyama, T; Wada, S; Ohashi, A; Satoh, Y; Ido, K; Sugano, K
Abstract : Background: When endoscopic retrograde cholangiopancreatography (ERCP) guided bile duct biopsy fails to demonstrate malignancy, it remains unclear how to manage patients with presumably malignant strictures. Aims: To evaluate the value of intraductal ultrasonography (IDUS) when bile duct biopsy is negative. Methods: Sixty two patients with strictures of the bile duct were studied prospectively. During ERCP, IDUS was performed using an ultrasonic probe (diameter 2.0 mm; frequency 20 MHz). Following IDUS, a bile duct biopsy was performed using forceps (diameter 1.8 mm). The IDUS images of the tumour were classified as polypoid lesions, localised wall thickening, intraductal sessile tumours, sessile tumour outside of the bile duct, or absence of apparent lesion. The bile duct wall structures at the site of the tumour as well as the maximum diameter of the tumour were also analysed. The IDUS findings were compared with the histological findings or clinical course. Results: When the IDUS images showed a polypoid lesion (n=19), localised wall thickening (n=8), intraductal sessile tumour (n=13), and sessile tumour outside of the bile duct (n = 20), the sensitivities of the biopsy were 80%, 50%, 92%, and 53%, respectively. Multiple regression analysis showed that the presence of sessile tumour (intraductal or outside of the bile duct: p<0.05), tumour size greater than 10.0 mm (p<0.001), and interrupted wall structure (p<0.05) were independent variables that predicted malignancy. Conclusion: When biopsy fails to demonstrate evidence of malignancy, the presence of sessile tumour (intraductal or outside of the bile duct), tumour size greater than 10.0 mm, and interrupted wall structure on IDUS images are factors that can predict malignancy.